Triathletes lose their advantageous pain modulation under acute psychosocial stress - Geva, N.; Pruessner, J.; Defrin, R. (Medicine & Science in Sports & Exercise, 2017)
Introduction: Triathletes, who constantly engage in intensely stressful sport, were recently found to exhibit greater pain tolerance and more efficient pain inhibition capabilities than nonathletes. However, pain inhibition correlated negatively with retrospective reports of mental stress during training and competition. The aim of the current study was to test pain inhibition capabilities of triathletes under acute, controlled psychological stress manipulation.